2014
DOI: 10.1111/jvim.12506
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Extracellular Fluid Volume in Healthy and Azotemic Cats

Abstract: BackgroundMethods for determining extracellular fluid volume (ECFV) are important clinically for cats. Bromide dilution has been studied in cats to estimate ECFV. Markers of GFR also distribute in ECFV and can be used for its measurement.Hypothesis/ObjectivesThe primary objective was to develop a method of determining ECFV from iohexol clearance in cats and evaluate agreement with that determined using bromide dilution. Additional objectives were to compare ECFV between azotemic and nonazotemic cats and evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Furthermore, a recent study suggested that extracellular fluid volume is not different between non-hyperthyroid cats with and without azotaemic CKD (Finch et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study suggested that extracellular fluid volume is not different between non-hyperthyroid cats with and without azotaemic CKD (Finch et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to amikacin, iohexol showed a slight but significant increase in V ss after fluid administration ( p = 0.008). Iohexol has previously been used as marker for the assessment of the extracellular fluid (ECF) volume ( Zdolsek et al, 2005 ; Finch et al, 2015 ). The volume of distribution of iohexol is hereby used as an indicator of the ECF volume.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the law of mass conservation, indicator-dilution techniques fulfill the mass balance principle at steady-state, whereby the total indicator mass following distribution in the fluid compartment will remain the same as the total mass injected into the compartment (80,85). Hence, the volume of a body fluid compartment can be estimated provided that the indicator's concentration following homogenous mixing can be accurately determined (84). Although exogenous indicator-dilution techniques are considered the conventional "gold standard" method for volume determination (17,86), they can result in hypersensitivity reactions and potential errors as a result of indicator extravasation, plasma turbidity, Hb contamination, or controversial back-extrapolation methods (18,(87)(88)(89)(90).…”
Section: One-volume Fluid Space Kinetic Modelmentioning
confidence: 99%
“…Although exogenous indicator-dilution techniques are considered the conventional "gold standard" method for volume determination (17,86), they can result in hypersensitivity reactions and potential errors as a result of indicator extravasation, plasma turbidity, Hb contamination, or controversial back-extrapolation methods (18,(87)(88)(89)(90). Radioactive isotopes are cumbersome to use and there is a significant time delay for exogenous indicators to equilibrate to a steady-state distribution (80,84). This precludes the ability to distinguish between the distribution and elimination phases (34,67) and does not permit analysis of acute dynamic fluid shifts (36).…”
Section: One-volume Fluid Space Kinetic Modelmentioning
confidence: 99%